O ensino de matemática nos anos iniciais a partir da prática do cotidiano - SILVA, Edianeide Fernandes da (Universidade Federal do Tocantins, 2021)
This research aims to understand how numeracy and literacy are worked with a view to student learning in relation to everyday practices. For this, we used the methodology of action researchand the qualitative approach. The subjects of the research were the students of the 3rd grade ofthe earlygrades of the afternoon period of the Municipal Center of Basic Education-CEMEB Professora Lívia Lorene Bueno Maia, and we also counted on the support of the class teacher during the whole process. Some theorists that supported this research were: Nacarato (2013), Pimenta (1999), Tripp (2005) among others. The development of this research is related to the group of studies on literacy and numeracy (GELEN). The research was described in nine episodes where the actions that were performed from the planning to the realization of the marketplace that took place in the last class are explained. To develop the research based on the learning obtained by participating in GELEN, the intention was, with the help of the class teacher, to work with the students in math classes on situations that would encourage them to think and calculate. The fundamental part was the materials used during the research, we chose to work with labels and packaging and with the students participation the products that would be used in the activities suggested in the lesson plan were collected, from this it was possible to perform the proposed activities with the interaction of all and also with the help of the classteacher. As a result of the research it was possible to notice that the students liked and managedto learn the content that was taught.